Draft Annual Plan 1988-89 Volume : VII Hill Areas Government of Assam - Planning Commission (Planning Commission, 1988)
The total provisions under agriculture research and education for Seventh Five year Plan is Rs.170.00 lakhs in the State Plan Schemes and Rs. 25.00 lakhs in Additive Plan. The Assam Agricultural University Complex located at Diphu under Karbi Anglong District has undertaken research works relevant to hill areas of Assam The agreed outlay during 1987-88 is Rs.35.00 lakhs in State Plan and Rs. 10.00 lakhs in Additive Plan.
Government of Assam, Development Commissioner for the Hill Areas